2018
DOI: 10.1016/j.amjcard.2018.04.061
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ambient Fine Particulate Matter Air Pollution and Colder Outdoor Temperatures on High-Density Lipoprotein Function

Abstract: Fine particulate matter (PM) air pollution and environmental temperatures influence cardiovascular morbidity and mortality. Recent evidence suggests that several air pollutants can promote dyslipidemia; however, the impact of ambient PM and temperature on high-density lipoprotein (HDL) function remains unclear. We hypothesized that daily exposures to higher levels of ambient PM and colder outdoor temperatures would impair HDL functionality. Lipoproteins, serum cholesterol efflux capacity (CEC), and HDL oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 31 publications
(56 reference statements)
3
18
0
2
Order By: Relevance
“…[86]. Moreover, the presence of cardiovascular risk factors, including hypercholesterolemia [13,60,87], obesity [88], diabetes type 1 and 2 [89,90], and even frequent exposure to pollution [91][92][93] or ethnicity have demonstrated to impact HDL properties and induce structural changes leading to variations in their subtypes profile. Altogether, these conditions may help explain the disappointing results observed in clinical trials aiming to increase HDL-c levels in secondary prevention.…”
Section: Impact Of Cardiovascular Risk Factor and Co-morbidities On Hmentioning
confidence: 99%
“…[86]. Moreover, the presence of cardiovascular risk factors, including hypercholesterolemia [13,60,87], obesity [88], diabetes type 1 and 2 [89,90], and even frequent exposure to pollution [91][92][93] or ethnicity have demonstrated to impact HDL properties and induce structural changes leading to variations in their subtypes profile. Altogether, these conditions may help explain the disappointing results observed in clinical trials aiming to increase HDL-c levels in secondary prevention.…”
Section: Impact Of Cardiovascular Risk Factor and Co-morbidities On Hmentioning
confidence: 99%
“…The current literature on PM-exposure and HDL functionality suggest that fine and ultrafine PM may impair functional properties of HDL via oxidative pathways [27,28,[30][31][32][33]. Accumulating evidence links particles to atherosclerosis, in particular those with a high amount of organic chemicals [3,6,31,36].…”
Section: Discussionmentioning
confidence: 99%
“…Results from a study by Mathew et al showed that exposure to even low levels of PM 2.5 (9,1 ± 1,8 μg/m 3 ) for a short period of time were linked to an impaired HDL functionality measured as cholesterol efflux capacity (n = 50) [27]. In the Beijing AIRCHD study, participants were followed up with 4 study visits in a 14-month period (n = 73).…”
Section: Epidemiological Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Of particular concern is the ambient fine particulate matter (PMs), a mixture of multiple components (such as metals, water-soluble ions, polycyclic aromatic hydrocarbons [PAHs] and organic carbons, etc.) and diversified sources (such as coal combustion, ground dust, biomass burning and vehicle exhaust) with high oxidative potential and small aerodynamic diameter (less than 2.5 micrometers) that can penetrate deep into the pulmonary microvascular system and affect various organ systems [14,15]. PMs are found to cause detrimental inflammation on various target organs through producing reactive oxygen species (ROS) [16][17][18].…”
Section: Introductionmentioning
confidence: 99%